Effects of a cycling intervention on adolescents cycling skills. (June 2022) - van Hoef, Tom; Kerr, Sonja; Roth, Ralf; Brenni, Claudio; Endes, Katharina
Abstract: Background: Over the last two decades, bicycling as a mode for transportation has declined by 64% among 16- to 20-year-old adolescents in Switzerland, the largest decrease of any age group. The aim of this study was to evaluate the short-term effects of a bicycle training on adolescents' cycling skills. In addition, the study investigated whether there is a relationship between school distance, mode of transport, bicycle use and cycling skills. Methods: 77 adolescents (Mean age = 17.1 ± 0.8 years) were assigned to the intervention group (n = 48) or control group (n = 29). In both groups, a validated practical cycling skills test was performed at baseline and 2 weeks after baseline. The intervention group performed 2 h of bicycle training one week after the baseline test. A questionnaire was used to determine bicycle use, mode of transportation and distance to school. Due to Covid-19 school closures, only an online questionnaire was administered at 6-month follow-up. To analyze the effects of cycling training on cycling skills, multiple linear regression models adjusted for age, gender, and baseline cycling skills were applied. Results: Compared to the control group, the total cycling skills increased in the intervention group (β = 4.54, [0.89 : 8.19], p = 0.02), as well as riding over a wooden plank with a ladder profile (β = 1.14, [0.08 : 2.19], p = 0.04) and controlled riding over a step (β = 1.48, [0.63 : 2.33], p ≤ 0.001). An association was found between bicycle use, mode of transportation, and cycling skills (p < 0.05). In contrast, no association could be found for school distance. Conclusion: Cycling training improved adolescents' cycling skills in the short term. Cycling skills correlated with bicycle use and mode of transportation. Highlights: The Swiss cycling promotion program DEFI VELO improves adolescents cycling skills. Adolescents cycling skills are positively associated with bicycle use. Use of public transportation is negatively associated with adolescents cycling skills. Cycling promotion programs should be implemented in school.